The Right to Privacy and Personal Data Protection in Russia, Lithuania and Germany: From History to Current Discourses - Rogers, Monika (Genocidas ir rezistencija, 2026)
This article discusses public and legal discourses related to ideas and perceptions of privacy and personal data security in Germany, Lithuania and Russia. It investigates whether – and if so, how – the historical ideas and beliefs about privacy and personal data protection are still shaping attitudes and policies related to personal data protection and privacy of these three countries. Russia, Lithuania and Germany had similar historical experiences of living in non-democratic societies. However, today Russia is drifting towards a completely opposite normative and geopolitical trajectory than Lithuania and Germany. The article reveals how differences in political systems affect legal agendas related to personal data protection. It also takes into consideration both similarities and differences between Germany and Lithuania.
Keywords: Personal Data Protection; Respect to Privacy; Human Rights; Law; History; Lithuania; Germany; Russia